Index and digital culture: Techno-creative paradoxes [índice y cultura digital: Paradojas tecno-creativas] - Vazquez Marquez , I. (2014)
This paper provides a theoretical discussion of the semiotic concept of index (in its double category of "reagent" and "designation") and its transformations in the digital era. To illustrate these transformations we take some examples from cinema, music and 3D virtual worlds, looking at the changes, mutations and indexical paradoxes that can be found in them.